Saberes tácitos na colheita manual do tomate: estudo de caso a partir da perspectiva da ergonomia - Silva, Fabiana Raulino da (2015)
The variability in agricultural work makes it difficult to be described without considering the complexity of it. Workers in tomato harvesting make the selection of the fruit distinguishing which tomatoes are suitable for harvest, which are not matured yet and which should be discarded, identifying the causes of defects and irregularities. These workers know the quality parameters without having any formal training. This knowledge is fundamental to regulate the strategies of these workers and should be enriched. This research shows a two-year period of immersion in the context of agriculture along with these workers, in order to analyze the importance of tacit knowledge involved in agricultural practice, understanding how this knowledge acquired in practice serve as the basis for all practical labor. As methodology, our study used ergonomics to understand the work of tomato pickers and identify how their knowledge guide the selection of the fruit for harvest. A multiple case study was conducted in three farms through the perspective of ergonomics. We used free observations through semi-structured interview and analysis of the speeches of workers to identify how this knowledge is transmitted and its importance. Our results show that workers must build a mental map, a reference in their mind of how a proper fruit look alike to be harvested. This representation brings several sensorial information that make them choose the fruit through its various features. Even without having received any formal training, the features identified in the fruit are the same listed in formal classification documents. It was noticed that although tacit knowledge is difficult to verbalize, women were able to express in a wider range of words the characteristics of the fruit that guided their actions. Learning of workers is intrinsically related to existing cooperation at work, as they teach each other in mutual aid during the execution of the harvest. For future work, we suggest other studies from ergonomics perspective, suggesting a work transformation to facilitate the sharing of knowledge of these workers.